PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PELECEHAN SEKSUAL - Musdalifa SamSam; Ilham Abbas; Baharuddin Badaru (Qawanin Jurnal Ilmu Hukum, 2020)
The research aims to examine and protect the law against children as a criminal act that commits a criminal act in the implementation of legal protection against child victims of criminal acts of sexual abuse. This research uses sociological or empirical research methods, data obtained from document studies and interviews with interested parties in the Makassar City Police and Makassar District Court, then a qualitative analysis is carried out. The results of this investigation show that legal protection for children as victims of criminal acts of sexual harassment in law enforcement practices by the Makassar City Police is a protection in the investigation process. Meanwhile, the legal protection by the Makassar District Court is in court prose. Obstacles in the implementation of legal protection against children as a criminal offense, namely, starting from the statement of the victim as a victim of sexual harassment, the law itself in this case regarding the law on child protection, as well as being technically obedient at the time of carrying out an investigation, in this case the process. the evidence. The recommendation of this research should be that the accountability of parents, family, and state government is a series of activities carried out continuously, integrated and coordinated by authorized institutions in an effort to fulfill the rights of children, especially children victims of sexual violence in order to protect children's rights. It is hoped that the law on child protection needs an amendment that is tailored to the existing legal needs.The research aims to examine and protect the law against children as a criminal act that commits a criminal act in the implementation of legal protection against child victims of criminal acts of sexual abuse. This research uses sociological or empirical research methods, data obtained from document studies and interviews with interested parties in the Makassar City Police and Makassar District Court, then a qualitative analysis is carried out. The results of this investigation show that legal protection for children as victims of criminal acts of sexual harassment in law enforcement practices by the Makassar City Police is a protection in the investigation process. Meanwhile, the legal protection by the Makassar District Court is in court prose. Obstacles in the implementation of legal protection against children as a criminal offense, namely, starting from the statement of the victim as a victim of sexual harassment, the law itself in this case regarding the law on child protection, as well as being technically obedient at the time of carrying out an investigation, in this case the process. the evidence. The recommendation of this research should be that the accountability of parents, family, and state government is a series of activities carried out continuously, integrated and coordinated by authorized institutions in an effort to fulfill the rights of children, especially children victims of sexual violence in order to protect children's rights. It is hoped that the law on child protection needs an amendment that is tailored to the existing legal needs.